The Impact of Buddhist Philosophy on Global Peace-building Efforts (Bodhi Path, 2025)
Buddhist philosophy, which emphasizes compassion, non-violence, and interdependence, has significantly impacted global peace-building efforts. Rooted in the teachings of the Buddha, key principles such as mindfulness (sati), loving-kindness (metta), and ethical conduct (sīla) offer a framework for resolving conflicts, fostering dialogue, and promoting harmony among diverse communities. This study examines the application of Buddhist teachings in contemporary peace-building practices, highlighting their influence on grassroots movements and international initiatives.Buddhist leaders and practitioners have historically emphasized the importance of addressing the root causes of conflict, such as greed, hatred, and ignorance. They believe that pursuing inner peace is essential for achieving societal peace. Modern examples of Buddhist-inspired peace-building include the contributions of figures like Thich Nhat Hanh, the Dalai Lama, and Sulak Sivaraksa. Their efforts in non-violent resistance, interfaith dialogue, and environmental advocacy have made a significant global impact.Buddhist-inspired mindfulness and meditation practices have become increasingly popular in conflict resolution workshops and trauma healing programs around the world. These practices offer tools to help foster empathy and understanding among conflicting parties. Additionally, international organizations like the United Nations have incorporated Buddhist principles into their peace-building frameworks, acknowledging their universal relevance.This paper discusses the challenges and opportunities of applying Buddhist philosophy to global peace efforts, especially in culturally and religiously diverse contexts. It emphasizes the transformative potential of Buddhism in fostering not only the absence of violence but also a comprehensive vision of peace based on mutual respect, compassion, and sustainable development. Ultimately, the research aims to demonstrate how the ancient wisdom of Buddhism continues to play a meaningful role in modern strategies for achieving global peace.
Keywords: Buddhist philosophy; Global peace building; Non-violence (Ahimsa); Compassion (Karuṇā); Mindfulness (Sati); Interdependence; Conflict resolution